Pengaruh Olah Tanah Dan Jarak Tanam Terhadap Pertumbuhan Dan Hasil Bawang Tiwai (Eleutherine americana Merr.) - Anita Rosita; Rustam Baraq Noor; Mahdalena Mahdalena (Universitas Widya Gama Mahakam, 2012)
Effect of tillage and plant spacing on growth and yield of onion tiwai (Eleutherine americana Merr.). The purpose of this study was to evaluate the response of the growth and yield of onion tiwai to the treatment and processing of soil and plant spacing parameters diperlakukan.Penelitian was conducted for 3 months starting in December 2009 until March 2010, research carried out in Loa Janan Ulu Kutai regency. This research is a randomized block design Plots Divided (RAK split plot) with 2 x 3 factorial design, each treatment was repeated three times, the first factor of tillage (T) is t0: without tillage (control) t1: with processing soil, while the second factor is the spacing of (J) is j1: 20 x 25 cm, j2: 25 x 30 cm and j3: 30 x 35 cm. The results showed that treatment of tillage (T) real berpengauh on plant height parameter ages of 30 and 60 days after planting, the number of chicks aged 60 and 90 days after planting, planting tuber number, tuber weight perpetak and tuber production tons per hectare, on plant height parameter of age 90 days after planting and the parameters of the number of seedlings 30 days after planting showed no significant effect. At the treatment plant spacing (J) on all parameters showed no significant effect, ie plant height ages 30, 60 and 90 days after planting, the number of chicks aged 30, 60 and 90 days after planting, the number of tubers, tuber weight and tuber production tons perpetak per hectare. Interaction between tillage and planting distance (T x J) also showed no significant effect on all parameters: plant height is age 30, 60 and 90 days after planting, the number of chicks aged 30, 60 and 90 days after planting, the number of bulbs, heavy perpetak bulbs and tubers production tons per hectare.